Discussion on the models of education of the reading in the first degrees inspired by the phonological conscience - Altamirano, Alfredo (2010)
This article raises questions about the relevance for the early grades of schooling models of reading instruction emerged from research on phonological awareness. Several studies have suggested the existence of different levels involved in reading. However, these levels are not seen in the early grades teaching practice guided by the models discussed here. Rather, these models point to an almost exclusive lexical learning of language, leaving aside the semantic construction processes that take place when reading. Phonological awareness is indeed vital for the acquisition of writing, however, to understand what is read not only requires understanding the words of the text read, but mainly to build the meaning of the text as read the sentences and paragraphs. From the line of work that began Emilia Ferreiro, the article states that children in the early grades themselves are able to perform these more complex processes, and the school should promote them. On the other hand, it is also discussing the educational relevance of these models, since it is very likely to be affecting a very significant rote learning and literacy instruction. That has raised the need to reflect properly on the relationship between psychological research and teaching practices for literacy. The pedagogy should make use of psychological contributions, but it must complement them considering other criteria necessary to facilitate learning.